Divine eloquence and human transformation : rethinking scripture and history through Gregory of Nazianzus and Hans Frei - Fulford, Ben. (Minneapolis : Fortress press, 2013)
"Key to a theology of scripture are the important issues of history, consciousness, rhetoric, and how theology functions in relation to interpretation of Christianity's religious texts. Seeking to address a critical problem in theology and the interpretation of scripture raised by modern historical consciousness, Ben Fulford argues for a densely historical and theological reading of scripture centered in a Christological rubric. The argument herein uncovers a figural pattern of divine action and presence in the sacred texts. Tracing the problem through the modern theological heritage, the author turns to a comparative account of theologically patterned reading represented by patristic theology in Gregory of Nazianzus and postliberal theology in its pivotal founder, Hans Frei. The book addresses the challenge of historicity and historical consciousness, argues for the relevance of pre-modern approaches to scripture, and offers a fresh and extensive account of two salient figures from the early and contemporary tradition, thus enacting a theology of retrieval as a resource on a present issue of vital importance" -- Publisher description.
The theological interpretation of scripture and the question of history -- God, Christ, and history in Gregory of Nazianzus -- The reshaping of history: Jesus Christ and the baptized life in Gregory of Nazianzus -- Distributing the word: Holy scripture and the preacher in Gregory of Nazianzus -- From letter to Spirit -- The rhetorical deployment of scripture in Gregory -- History, biblical narrative, and the shaping of identity in Hans Frei -- History and holy scripture in Hans Frei -- Divine eloquence.
Includes bibliographical references (pages 283-295) and index.
Keywords: Gregory, -- of Nazianzus, Saint; Frei, Hans W; Frei, Hans W..; Gregory, -- of Nazianzus, Saint..; Bible -- Hermeneutics; Bible -- Theology; Bible..; Hermeneutics..; Theology..